K, Rb, Sr, Th, and U contents of the basement rocks from the Yamato Mountains, East Antarctica - Kazuyuki Shiraishi; Hiroshi Kanaya (National Institute of Polar Research, 1983)
Sixty-three samples of basement rocks collected from the Yamato Mountains were analyzed for the trace elements Rb, Sr, Th and U together with K. The element abundances and ratios are different among the syenitic rocks. The Sr content of the clinopyroxene quartz monzonite, in particular, is considerably high. Mutual differences of the element abundances and ratios among the metamorphic rocks are not significant, and the ranges of the values seem to be consistent with those of lower granulite to upper amphibolite facies rocks in the shield areas of the world.